Batu pahat car workshops finder - Lee, Wei Chuan; Kasim, Shahreen; Seah, Choon Sen; Hassan, Rohayanti; Mohd. Ali, Norhayati (UTM Press., 2017)
Batu Pahat Car Workshops Finder is an application for driver to find the nearest car workshops with the current location and can get GPS navigation to the selected car workshop. The proposed application is because lots of car breakdown problem are appearing among the car, this problem become worst when driver is at some unfamiliar place. Therefore, Batu Pahat Car Workshops Finder is an application for user to solve the problem. The application helps user to repair their car while travelling and suddenly the car breakdown and they did not find any car service or repair station nearby. With this application, it will show the available car workshops nearby at user’s current location along with their contact number.